The existence of the Pancasila ideology in counteracting the nature of racism which leads to terrorism among the younger generation - fitria, ratna (Universitas Pendidikan Indonesia, 2019)
the involvement of young people, especilly those who are educated in act of terrorism, makes us realize that the young generation is very far from the ideology of pancasila. The moral crisis is engulfing this nation and needs to be corrected immediately. in the process of improvement we must know what is the background of the incident and why young people can be involved in the terrorism